PENGARUH INTENSITAS MODAL, KEPEMILIKAN MANAJERIAL, LEVERAGE, FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Seran, Angelina Pindy; Suwarti, Titiek (Faculty of Economic and Business Universitas STIKUBANK, 2024)
The aim of this research is to examine the impact of capital intensity, managerial ownership, leveragee and financial distress on the level of application of conservatism used in manufacturing companies listed on the BEI from 2020 to 2022. The population of this research is manufactur companies listed on the BEI. The method of this research used a purposivee sampling method, totaling 66 companies were used as samples. The panel regression model was used in data analysis, to assess the feasibility of the model using the F test and coefficient of determination. The research results of the hypothesis show that capital intensity has a significant positive impact on the application of accounting conservatism. in contrast, managerial ownership, leverage, and financial distress have no impact on accounting conservatism